The Influence of Employee Well Being, Emotional Intelligence and Job Simplification on Employee Performance with Employee Achievement as an Intervening Variable on Employees of Tritya Eye Clinic Surabaya - Fina Aprilia; Siti Mujanah; Sumiati Sumiati (Harmony Management: International Journal of Management Science and Business, 2025)
Tritya Eye Clinic Surabaya, as one of the developing eye health service providers today, faces a major challenge in providing optimal services for various patient segments, including BPJS Kesehatan participants, private insurance users, and general patients. Problems that occur with employees at the Tritya Eye Clinic, based on the results of a psychological test on September 9, 2024 on 24 employees, it was found that 22 employees had low/lacking emotional stability, in addition, based on personnel data in 2024, it was found that there were employees who committed violations with one of the causes being emotional stability based on the results of counseling conducted by the Head of HR. From the counseling, it was also found that employees have a desire for their well-being in the workplace, which is a trigger for expectations related to employee well-being and digitalization requires Tritya Eye Clinic to make changes that are expected to simplify work and minimize errors in work. The purpose of this study was to determine the effect of employee well being , emotional intelligence and job simplification on employee performance with employee achievement as an intervening variable on employees of Tritya Eye Clinic Surabaya. This study uses a quantitative method with primary data sources obtained from distributing questionnaires. The population of the study was employees of Tritya Eye Clinic Surabaya. The selection of respondents was carried out using the saturated non-probability sampling method with a total of 67 respondents . The data analysis method used descriptive analysis and SEM-PLS analysis. The results showed that the variables employee well being , emotional intelligence and job simplification had a positive and significant effect on employee performance through employee achievement on employees of Tritya Eye Clinic Surabaya.